Paediatric presentation and outcome of congenital protein C deficiency in Japan. (4th February 2013) - Ohga, S.; Kang, D.; Kinjo, T.; Ochiai, M.; Doi, T.; Ishimura, M.; Kayamori, Y.; Urata, M.; Yamamoto, J.; Suenobu, S.‐I.; Kanegane, H.; Ikenoue, T.; et al.
Summary Severe heritable protein C (PC) deficiency is quite rare, although heterozygous PROC mutation is the second leading cause of genetic predisposition to thrombosis in Japanese adults. The aim of the study was to search the optimal management, the paediatric onset and outcomes of PC deficiency were characterized in Japan. The genetic study, postmarketing survey of activated PC (aPC) concentrate (Anact®C) and intensive review in Japan for 20 years enabled the analysis of the disease onset, genotype, treatment and prognosis. Symptomatic PC deficiency was determined in 27 Japanese children. All but two patients presented within 16 days after birth (three prenatal and six neonatal onsets). Postnatal‐onset cases had normal growth at full‐term delivery. Of the 27 patients, 19 suffered intracranial thrombosis or haemorrhage (ICTH) (three foetal hydrocephalies), 16 developed purpura fulminans (PF) and 10 had both at the first presentation. ICTH preceded PF in both affected cases. Low PC activities of 18 mothers and/or 12 fathers indicated 20 inherited PC deficiencies (2 homozygotes, 11 compound heterozygotes and 7 heterozygotes) and seven unidentified causes of PC deficiency. Nine of 11 patients studied had PROC mutations. Four unrelated patients (50%) carried PC nagoya (1362delG). No PC‐deficient parents had experienced thromboembolism. Of the 18 patients with aPC therapy, two died and eight evaluable survivors had neurological sequelae. This first comprehensive study of paediatric PC deficiency suggested that perinatal ICTH was the major presentation, occurring earlier than neonatal PF. PC nagoya was prevalent in paediatric, but not adult, patients in Japan. Early maternal screening and optimal PC therapy are required for newborns at risk of PC deficiency.